ANALISIS PEMILIHAN SUPPLIER BAHAN BAKU TERBAIK PT GRAFIKA PRIMA BERDASARKAN NILAI BOBOT TERTINGGI DENGAN METODE AHP DI PT. GRAFIKA PRIMA - Nur Aini Ismiranda; Herlina Herlina (LPPM Universitas Bina Bangsa, 2023)
PT, Grafika Prima, is a company engaged in the packaging product. Established since 2018 and has a total of 90 customers. PT. Grafika Prima requires suppliers who always meet the needs of raw materials according to the company's criteria. This manufacturing industry uses cardboard as its main raw material. PT. Grafika Prima is experiencing struggles in determining suppliers of raw materials according to the company's criteria. AHP (Analytical Hierarchy Process) is a suitable method in solving problems faced by companies because it relates to rank criteria based on weight values. Software of Expert Choice 11 which is useful in weighting values. Thus, the results of the criteria prioritized by the company are Flexibility criteria with the highest weight value of (0.35), quality (0.28), delivery (0.14), service (0.12), and price (0.07 ). Meanwhile, suppliers who are able to meet the company's needs based on the calculation of the highest criteria and sub-criteria are PT Naga Putra Packindo with a weight value of (0.160), PT Rapipack Asritama (0.140), PT Makmoor Jaya Usaha (0.1380), PT Prima Ptr (0.131) , UD Restu Abadie (0.1220), PT Karya Kartoon (0.110), PT Andalan Ajas Pratama (0.100), and CV Berkat Marya (0.070).